Segredos da alma: a dádiva da assistência de Enfermagem - Almeida, Sheyla Gomes Pereira de (2006)
The present study is an analysis of interpersonal relationships between the nursing staff and the patients under their care. Its objectives are to analyze ties/links that may possibly exist in such relationships and to describe, based on the experience of the patients, how they are received by the nursing staff, and what is the extent of their reliability on the nursing staff within the hospital. This investigation is analytical in nature and qualitative in approach, having as its leading thought Marcel Mauss s gift-exchange theory. The study involved eighteen in-patients, eight of them from government institutions, at a large hospital school and ten others from a private specialty hospital; both in the city of Natal, state of Rio Grande do Norte, Brazil. Data were collected between January and March 2006. Results point to ties being created between the nursing staff and patients irrespective of their social status, involving especially the development of friendship and reliability. We have noticed that in both services the interpersonal relationship is associated with the circulation of the symbolic goods mentioned in the patients discourse, such as attention, loving care and concern, among others, marking the formation of ties during hospital stay. Likewise, reliability is also present in close relationship with the technical competence of the professional. Patient hospitality is associated with the manner in which the patients were treated on being admitted to the hospital, although they also refer to hospitality at later moments, during the course of their treatment. Finally, we are in a position to say that there are ties/links between in-patients and nursing staff, irrespective of the patient s social status and class divide. It is thus evident that the antiutilitarian symbolism of gift to give, receive, give back -, which shapes the setting of social ties also takes place in today s utilitarian, individualistic and competitive societies. Thus, human beings whose existence is dependent on mutual relationships try to save their humanity, especially those who are fragile and dependent as is the case of the hospital in-patient